South-South economic cooperation : regional trade agreements among developing countries. - KOTSCHWAR, Barbara R. (1995)
Examines the future direction of South-South trade. Cites three reasons for long-term gains from regional trade arrangements, viz. (1) economies of scale; (2) political economy; and (3) rationalization of industrialization. Explores these argument for regional trade arrangements by examining the MERCOSUR and the Preferential Trade Area of Eastern and Southern Africa, and the Southern African Development Community.